Adoption of e-Government in the Republic of Kazakhstan - Yerlan Amanbek; Ilyas Balgayev; Kanat Batyrkhanov; Margaret Tan (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Information and Communication Technology has been gaining importance in the economy of Kazakhstan, the largest landlocked country. In this paper, we investigate the factors that influence Kazakhstan's e-Government portal use at the informational stage and describe the challenges encountered by citizens while using the portal. Statistical analysis is performed on a web-based questionnaire survey targeted at citizens of Kazakhstan. The technology acceptance model is used as a methodology to measure attitude towards portal usage. This paper also discusses the barriers that can restrict the successful adoption of e-Government services. The results show that awareness among citizens is high and they perceive the portal to be useful, but only a limited percentage of citizens actually use it regularly. The results of this paper could be used to help the IT managers of the portal to improve the management of informational content and maintain more effective adoption among citizens.
Keywords: 650; e-Government; Technology Acceptance Model (TAM); The Republic of Kazakhstan